Ghana : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report, 2021)
Ghana has been hit hard by the pandemic. The government's proactive response helped contain the spread of COVID-19, protecting lives and limiting the impact on economic activity. However, partly because of the pandemic, the fiscal position worsened considerably last year, with a sharp increase in public sector debt.